Surface-Mediated in Situ Metalation of Porphyrins at the Solid-Vacuum Interface - Marbach, Hubertus (Accounts of Chemical Research, 2015)
The investigation of porphyrin derivatives at the solid-vacuum interface has become a vivid research field with the prospect to tailor functional molecular architectures and as prototype examples to study the fundamental properties of porphyrin derivatives in regard to their vital role in many natural processes. The functional properties of the porphyrin derivatives are mainly determined by the central metal atom. Thus, the recent exploration of the surface-confined in situ metalation of porphyrins is an important step toward the realization of molecule-based functional devices. The corresponding metalation reaction of free base porphyrin derivatives can be conveniently realized in situ in ultrahigh vacuum by post- or predeposition of metal atoms or directly with substrate atoms in the so-called self-metalation. Moderate heating above room temperature (RT) might be necessary either to realize the transport of the metal to the porphyrin via diffusion or to overcome an activation barrier determined by the redox reaction itself. Surface science techniques like scanning tunneling microscopy (STM), X-ray photoelectron spectroscopy (XPS), and temperature-programmed desorption (TPD) are powerful tools to scrutinize the reaction and give valuable insights into the metalation process. For example, the completed metalation can be reflected in an enhanced apparent height of the corresponding porphyrin in STM or can be evidenced by characteristic changes in the N 1s region in XPS. These signatures allow monitoring of the progress of the metalation, and it was found that the reaction generally proceeds with very high yield. Surface diffusion of the coadsorbed metal atoms mediates the reaction and is crucial for the high yields of the corresponding reactions with pre- and postadsorbed metals. It was also demonstrated that the completed metalation can indeed significantly alter the adsorption behavior and the electronic properties and thus the functionality of the porphyrin molecules. These alterations can be used to monitor the kinetics of a particular porphyrin self-metalation reaction by STM and to estimate the activation barrier for that reaction based on isothermal measurements at different temperatures. Also TPD measurements of the H2 and D2 signals allow for the determination of corresponding activation energies for the metalation of free base porphyrins and their deuterized analogues. Gas phase DFT calculations of the metalation of the free base porphyrin macrocycle identify intermediate reaction steps with the transfer of the first hydrogen atom to the metal center being the main barrier to overcome. The values from these calculations are in fair agreement with experimentally determined ones. However, TPD based results indicate that exchanges of deuterium and hydrogen between the central nitrogen and the surface occur, which indicate an active role of the surface and challenge the findings from gas phase DFT. The in situ metalation of porphyrins at the solid-vacuum interface is established as a novel and convenient route to tailor functional molecular architectures. With different surface science techniques detailed insights into the surface-mediated metalation reaction were achieved for this class of prototype functional molecules.
EAM Import::2019-03-12